Regional economic integration :the emerging market crisis and stock market linkages - Patricia Oh Swee, Ling (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study empirically investigates the relationship between the ASEAN-5 stock markets. With the adoption of the monthly price series of Composite Indexes spanning since 1987:1 to 2006:12, the results show that the 1997 Asian financial crisis did significantly affected the integration process of the ASEAN-5 stock markets. One cointegrating vector was found for the pre-crisis period. However, neither the full sample nor the post-crisis period indicates that the ASEAN-5 stock markets are integrated. In addition, there was a short-run causal relationship between the markets whereby Philippines seems to market lead the rest of the ASEAN-5 stock markets except for the Singapore’s market. On the other hand, Malaysia is somehow the market follower within this region. Overall, a beneficial international investment portfolio diversification within the context of the ASEAN-5 equity markets does actually exist.